Does Earnings Quality Affect Information Asymmetry: Evidence from Trading Costs - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2008)
The adverse consequences of poor earnings quality have been the subject of significant debate among academics, practitioners and regulators. However, the empirical evidence on pricing implications of earnings quality is sparse and controversial. We examine one potential consequence of poor earnings quality - its impact on information asymmetry. We document that poor earnings quality increases the adverse selection risk as manifested in trading costs and lowers liquidity in financial markets. Both innate and discretionary components of earnings quality contribute significantly to information asymmetry. Further, poor earnings quality exacerbates information asymmetry around earnings announcements, especially for firms where earnings represent the principal source of information for market participants, suggesting that poor quality earnings offers a greater information advantage to informed traders. An important implication is that earnings quality can affect cost of capital via its impact on trading cost. Additionally, from a policy perspective, we show that earnings quality can lead to significant variation in information asymmetry even for firms within a uniform reporting regime.